Technological Innovation to Support 21st Century Learning Outcomes and Sustainability at Universitas Islam Negeri (UIN) Antasari - Herman Sjahruddin; M Ramli; B.M.A.S. Anaconda Bangkara; Nawassyarif Nawassyarif; Endang Fatmawati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This study analyzes how technological innovation supports and improves student learning outcomes and sustainability at Universitas Islam Negeri (UIN) Antasari. This study obtained data from interviews with senior lecturers and researchers and 12 resource persons, and 12 open questions. We conducted a series of questions for interviews and a literature study to understand how this change occurred. Next, the researchers analyzed the interview results with a phenomenological approach; to ascertain how technological innovation supports 21st-century learning in higher education. Based on the existing data and discussion, concluded that technological innovations such as the internet and digital applications currently in academic activities in the distance learning process and student face-to-face classes strongly support that goal. This considers the penetration of the internet and computer technology used in learning and teaching. With the experience of lecturers and students at UIN Antasari. Technological innovation supports learning there with the clear advantages of existing technology. Thus, it is hoped that the results of this study be helpful to improve the quality of further research. Keywords: Technological Innovation, 21st-Century Learning Outcomes, Learning Outcome